ACCEPTANCE OF BLOCKCHAIN TECHNOLOGY IN SUPPLY CHAIN MANAGEMENT IN INDONESIA: AN INTEGRATED MODEL FROM THE PERSPECTIVE OF SUPPLY CHAIN PROFESSIONALS FOR SUSTAINABILITY - Uce Karna Suganda; Herry Achmad Buchory; Zaenal Aripin (KRIEZ ACADEMY : Journal of development and community service, 2024)
Blockchain technology is a significant breakthrough in the world of modern supply chain management. In the Indonesian context, this study places emphasis on the acceptance of blockchain technology by professionals in the supply chain industry. The research is based on the understanding that efficient supply chain management is an essential element of business success in the current era of globalization. The integrated model developed in this research involves an inclusive approach that takes into account multiple perspectives from supply chain professionals. In the process, we analyze the level of acceptance of blockchain technology, identify the benefits that this technology can provide, and illustrate the potential role of blockchain in improving sustainability in the supply chain. The results show that the acceptance of blockchain technology in Indonesia is positive. Supply chain professionals recognize the added value that this technology can provide in improving transparency, security, and efficiency in their supply chains. The integrated model proposed in this study provides valuable guidance for Indonesian supply chain practitioners in implementing blockchain technology in their operations. As such, this research makes an important contribution to the understanding of the acceptance of blockchain technology in the context of supply chain management in Indonesia, which can support steps towards a more efficient, transparent, and sustainable supply chain in the future.